ISOLASI DAN IDENTIFIKASI AWAL SENYAWA INHIBITOR RNA HELIKASE VIRUS HEPATITIS C DARI EKSTRAK BUAH MANGROVE Avicennia marina (Forsk.) Vierh - Apon Zaenal Mustopa; Melki .; Ika Sari Kusumawati (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
Hepatitis C virus is the cause of hepatitis C disease which has high virulence. Recent therapy using combination of ribavirin and alpha interferon has short efficiency (< 80%). Thus, the discovery of new drug is needed. Antiviral drugs can be discovered through molecular target therapy by finding the inhibitor of RNA helicase that play role in viral replication. Inhibitor can be derived from chemical compound produced by mangrove. The aim of this research was to isolate the active compound groups from fruit of Avicennia marina (Forsk) which had inhibitory activity against RNA helicase. Inhibitory activity was measured by releasing of phosphate inorganic in colorimetric ATPase assay. Crude extract was fractionated using gel filtration chromatography with methanol in chloroform solvent. The result showed that fraction 2 has the highest inhibitory activity i.e. 81.78%. Phytochemical test of crude extract indicated positive result for flavonoids, alkaloids, steroid dan triterpenoid, tannin and saponins. Moreover, high performance liquid chromatography (HPLC) analysis showed absorption peak with the high abundance at the retention time of 7.250; 18.983 and 20.050 minute at 216 nm, 247 nm and 263 nm, respectively. According to the results of phytochemical, TLC, and HPLC analyses, inhibitor compound from fruit of A. marina (Forsk) was suggested it belongs to flavonoids.Key words: Avicennia marina, flavonoid, hepatitis C virus, RNA helicase